The immunology of solid organ transplantation. Issue 8 (August 2021) - Wubetu, Jonathan T.; Brown, Christopher E.; Clancy, Marc
Abstract: Solid organ transplantation has progressed dramatically over the last 50 years; however, rejection still remains one of the barriers to successful transplantation. Immunological processes underlying the mechanisms of rejection are well described and numerous pharmacological agents exist to help suppress a recipient's immune system in order to prolong graft survival. Furthermore, clinician decisions and actions during both the work-up of a potential transplant recipient and in the perioperative phase can impact upon the immunological status of an individual and the likelihood of successful solid organ transplantation. In this article we aim to describe the key processes involved in solid organ immunology and their relevance in anaesthetic practice.